Reck enables cerebrovascular development by promoting canonical Wnt signaling - Ulrich, Florian (Development, 2016)
The cerebral vasculature provides the massive blood supply that the brain needs to grow and survive. By acquiring distinctive cellular and molecular characteristics it becomes the blood-brain barrier (BBB), a selectively permeable and protective interface between the brain and the peripheral circulation that maintains the extracellular milieu permissive for neuronal activity. Accordingly, there is great interest in uncovering the mechanisms that modulate the formation and differentiation of the brain vasculature. By performing a forward genetic screen in zebrafish we isolated no food for thought (nft (y72)), a recessive late-lethal mutant that lacks most of the intracerebral central arteries (CtAs), but not other brain blood vessels. We found that the cerebral vascularization deficit of nft (y72) mutants is caused by an inactivating lesion in reversion-inducing cysteine-rich protein with Kazal motifs [reck; also known as suppressor of tumorigenicity 15 protein (ST15)], which encodes a membrane-anchored tumor suppressor glycoprotein. Our findings highlight Reck as a novel and pivotal modulator of the canonical Wnt signaling pathway that acts in endothelial cells to enable intracerebral vascularization and proper expression of molecular markers associated with BBB formation. Additional studies with cultured endothelial cells suggest that, in other contexts, Reck impacts vascular biology via the vascular endothelial growth factor (VEGF) cascade. Together, our findings have broad implications for both vascular and cancer biology.